Cellular Stress Responses and Monitored Cellular Activities. Issue 2 (August 2016) - Sawa, Teiji; Naito, Yoshifumi; Kato, Hideya; Amaya, Fumimasa
Abstract : ABSTRACT: To survive, organisms require mechanisms that enable them to sense changes in the outside environment, introduce necessary responses, and resist unfavorable distortion. Consequently, through evolutionary adaptation, cells have become equipped with the apparatus required to monitor their fundamental intracellular processes and the mechanisms needed to try to offset malfunction without receiving any direct signals from the outside environment. It has been shown recently that eukaryotic cells are equipped with a special mechanism that monitors their fundamental cellular functions and that some pathogenic proteobacteria can override this monitoring mechanism to cause harm. The monitored cellular activities involved in the stressed intracellular response have been researched extensively in Caenorhabditis elegans, where discovery of an association between key mitochondrial activities and innate immune responses was named "cellular associated detoxification and defenses (cSADD)." This cellular surveillance pathway (cSADD) oversees core cellular activities such as mitochondrial respiration and protein transport into mitochondria, detects xenobiotics and invading pathogens, and activates the endocrine pathways controlling behavior, detoxification, and immunity. The cSADD pathway is probably associated with cellular responses to stress in human inflammatory diseases. In the critical care field, the pathogenesis of lethal inflammatory syndromes (e.g., respiratory distress syndromes and sepsis) involves the disturbance of mitochondrial respiration leading to cell death. Up-to-date knowledge about monitored cellular activities and cSADD, especially focusing on mitochondrial involvement, can probably help fill a knowledge gap regarding the pathogenesis of lethal inflammatory syndromes in the critical care field.